التأصيل المفاهيمي للتراث الصوفي ومنطلقاته التاريخية - بولعراس, جباري; حمادي, هواري (جامعة الوادي - University of Eloued, 2021)
إن قراءة التراث الصوفي من منظور تاريخي يكشف البعد الروحي للإنسان منذ نشأته الأولى، وطالما كان الاهتمام بالصفاء القلبي وتزكية الروح يترجم القيم الأخلاقية للمجتمعات السامية وعبر مختلف الحضارات، وهذا الاهتمام بالجوانب الكوثرية و الروحية تجعل الإنسانية عبر أجناسها المتعددة تتألف و تتراحم مشكلة بذلك تناغم كوني واحد. التراث، التصوف، التاريخ، الروح، الحضارة. Reading the Sufi heritage from a historical perspective reveals the spiritual dimension of man from its very beginning, and as long as the interest in heartfelt serenity and the recommendation of the spirit translates the moral values of high societies and across different civilizations, this interest in the cothyre and spiritual aspects makes humanity across its multiple races consist of a problem thus a single universal harmony.
مقال
Keywords: التراث، التصوف، التاريخ، الروح، الحضارة; Heritage, mysticism, history, spirit, civilization